THU0060 The Relationship between Adherence To A Treat-To-Target Approach for Clinical Care of US Patients with Rheumatoid Arthritis and Achievement of Low Disease Activity. (15th July 2016) - Harrold, L.R.; Reed, G.W.; John, A.; Barr, C.J.; Saunders, K.C.; Soe, K.; Magner, R.; Greenberg, J.D.; Kremer, J.M.
Abstract : Background: Little is known about the relationship between adherence to the treat-to-target (T2T) paradigm and clinical outcomes in US patients with rheumatoid arthritis (RA). Objectives: To evaluate the relationship between adherence to T2T care and achievement of low disease activity (LDA) using a post hoc analysis of a cluster-randomized behavioral intervention trial evaluating a T2T implementation approach vs usual care (UC) in patients with RA. Methods: Twenty-eight rheumatology practices from the Corrona network recruited patients with RA between July 29, 2011, and July 30, 2013. Eligible patients with moderate or high disease activity (Clinical Disease Activity Index [CDAI >10]) were followed for 12 months. Regardless of randomization in the trial (T2T vs UC), sites were categorized based on rate of acceleration (e.g., initiation or dose increase of cDMARD or biologic at visits with CDAI >10 and no treatment acceleration in the prior 3 months). Sites that accelerated therapy at ≥60% of eligible visits (top tertile) were considered high acceleration (HA) sites; sites with <60% acceleration rates were deemed low acceleration (LA) sites. The primary endpoint was achievement of LDA (CDAI ≤10) at 12 months. Baseline characteristics of the groups were compared using standardized differences. An intent-to-treat analysis was performed with logistic regression models adjusting for clustering by site and covariates associated with |standardized differences| >0.10. As a sensitivity analysis, logistic regression models were fitted using acceleration rates as a linear association. The first model was as a continuous covariate (1 unit representing a 10% change in acceleration). The second model allowed for a threshold effect and used a linear spline with a knot at 60% acceleration. Results: Overall, there were 10 HA sites (195 patients) and 18 LA sites (337 patients). The groups were similar in terms of sex, race, ethnicity and baseline disease activity. However, HA site patients were younger (mean age, 56 vs 58 years) and had shorter disease duration (mean, 6 vs 9 years). Over the study period, 17% of HA site patients (34/195) and 18% of LA site patients (62/337) dropped out ( P =0.832). The rates of achievement of LDA at the last visit were 60.5% in the HA group vs 52.5% in the LA group (odds ratio [OR] 1.78; 95% CI 0.96–3.27) in multivariable models adjusting for demographics and disease characteristics. In the sensitivity analyses, use of acceleration rate as a continuous covariate was associated with an OR of 1.15 (95% CI 0.99–1.24). In the model with the spline (Figure ), acceleration rates <60% were associated with an OR of 0.98 (95% CI 0.78–1.21), while rates ≥60% had an OR of 1.73 (95% CI 1.13–2.66). Conclusions: Increased site adherence to a T2T approach was associated with a greater likelihood of achieving LDA. Evidence suggests there may be a threshold effect, indicating a lack of benefit with inconsistent adherence to the T2T approach. Acknowledgement: The Corrona T2T study is sponsored by Corrona, LLC, with support from a development and subscription agreement/contract with Genentech and additional support from AbbVie and Crescendo. Disclosure of Interest: L. Harrold Grant/research support from: Corrona, LLC, Employee of: Corrona, LLC, G. Reed Employee of: Corrona, LLC, A. John Employee of: Genentech, Inc, C. Barr Employee of: Corrona, LLC, K. Saunders Employee of: Corrona, LLC, K. Soe Employee of: Corrona, LLC, R. Magner: None declared, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: AstraZeneca, Celgene, Genentech, Janssen, Novartis, Pfizer, Employee of: Corrona, LLC, J. Kremer Shareholder of: Corrona, LLC, Grant/research support from: Genentech, Inc, Consultant for: AbbVie, Amgen, BMS, Genentech, Lilly, Pfizer, Employee of: Corrona, LLC